Crystal growth, guest ordering and ferroelastic properties of urea inclusion compounds - Rush, Jeremy Richard (Kansas State University, 2007)
The ferroelastic urea inclusion compound (UIC) of 2,10-undecanedione/urea exhibits a striking pseudoelastic memory effect. Although pseudoelasticity is possible for UICs containing only 2,10-undecanedione, introduction of a structurally similar guest impurity (2-undecanone) gives rise to rubber-like behavior, a form of pseudoelasticity. This phenomenon depends on both the crystal strain and the concentration of monoketone: above 13-14% 2-undecanone, pseudoelastic behavior is observed reliably, even at strains as high as 2.4%. The dramatic change in ferroelastic behavior over a small range of impurity content indicates that this is a critical threshold phenomenon. Because the impurity concentration has such a dramatic effect on domain switching, it was important to determine the sector-dependent patterns of incorporation of this relaxive impurity. Preliminary HPLC analyses of guest populations suggest that preferential incorporation of monoketone guests occurs between nonequivalent growth sectors, and that these patterns can be rationalized using a symmetry specific growth model. Birefringence mapping and HPLC studies of optically anomalous UICs containing mixtures of 2,9-decanedione and 2-decanone (which possess trigonal metric symmetry) suggest analogous patterns in guest incorporation and/or ordering that can also be rationalized. Although crystals of 2,9-decanedione/urea exhibit no ferroelastic strain at ambient temperature, they exhibit a proper ferroelastic phase transition near -170[degrees]C. It is proposed that differential perfection of domains gives rise to pseudoelasticity in UICs, and that relaxive impurities play an important role in the energetics of this process. Because ultrafast video studies of domain reversion kinetics demonstrate no clear correlation of observed rates with impurity content, it is proposed that the relaxive impurities facilitate spontaneous domain reversion by annealing stressed defect sites that would otherwise lead to irreversible or plastic domain switching. Following earlier work using synchrotron white beam X-ray topography, the driving force for domain reversion is thought to involve the presence of nanoscopic twins whose strain is epitaxially mismatched with neighboring daughter domains. The behavior of these nanoscopic twins was monitored with in-situ X-ray diffraction studies of stressed crystals, and this has led to a more thorough understanding of the role of these nanoscopic twins in the ferroelastic domain switching and rubber-like behavior in this class of materials.
Keywords: ferroelastic domain switching; pseudoelastic memory effect; rubber-like behavior; guest impurity; preferential incorporation; symmetry specific growth model; Chemistry, Organic (0490)